Difficult-to-treat OSAS: Combined continuous positive airway pressure (CPAP) and mandibular advancement devices (MADs) therapy. A case report. Issue 3 (3rd May 2020) - Luzzi, Valeria; Brunori, Marco; Terranova, Sergio; Di Paolo, Carlo; Ierardo, Gaetano; Vozza, Iole; Polimeni, Antonella
ABSTRACT: Background : Obstructive sleep apnea syndrome and is characterized by recurrent episodes of partial or complete upper airway collapse during sleep with consequent oxygen desaturations and cardiovascular, neurological, and metabolic impairment. Clinical presentation : The authors report the case of a 66-year-old male presenting "metabolic syndrome" (obesity, impaired glucose tolerance, dyslipidemia, multi-drug treated arterial hypertension), atopy, mouth breathing due to turbinate hypertrophy, and pathological daytime sleepiness. As patient's compliance to standard continuous positive airway pressure (CPAP) therapy was poor, he was treated using low-pressure CPAP combined with a mandibular advancement device (MAD). Conclusion : In selected patients, a treatment combining CPAP and MAD might be a more tolerable alternative to CPAP alone. The improved pharyngeal patency, promoted by mandibular advancement and stretching of the pharyngeal muscles, allows operating the CPAP at lower pressures when the MAD alone is not sufficient to induce a safe sleep profile.